Imaging Findings of a Rare Case of an Infected Urachal Diverticulum - Fraser Gomes; Sushmitha Prasad; Jenikar Paulraj; Harshavardhan Balaganesan; Kushbu Sony (International Journal of Anatomy Radiology and Surgery)
A 26-year-old female patient was referred to the Department of Radiodiagnosis, Shri Sathya Sai Medical College and Research Institute, Chennai, Tamil Nadu, India. with complaints of severe right iliac fossa and pelvic pain, fever, nausea and vomiting since a week. Physical examination revealed tenderness predominantly in the lower abdomen. Initial work-up, which included chest and abdominal plain radiographs, was normal.